Molasses associated the inoculation of efficient microorganisms in initial development of Cashew tree - Araújo, Vinícius de Sousa; Rezende, Jefrejan; Nobre, Rafael de Sousa; Santos, Cássio de Moura; Carvalho, Ana Clara Caminha de; Veloso, Ronilson Carvalho; Sousa, Vicente de Paula Canela de (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Cashew tree is considered one of the most important fruit crop in the semi-arid regions of tropical climate in the world. The low levels of crop productivity are linked to the semi-arid climate, inadequate management of correction and fertilization and the non-adoption of sustainable forms of cultivation. In view of this, organic fertilizer emerges as a promising alternative source. Sugarcane molasses is residue rich in minerals, is easy to handle, inexpensive and of has great agricultural potential. Efficient microorganisms, community of microorganisms naturally found in fertile soils and in plants, can also be key parts in the biological processes of the soil, favoring its fertility and consequently the development of plants. In this context, the objective was to evaluate the initial development of cashew trees in response to the application of sugarcane molasses associated with the inoculation of efficient microorganisms. The experimental design used was completely randomized, with four replications and the treatments organized in a factorial arrangement (4 x 2), being formed by the combination of four doses of molasses (0, 1/2, 1 and 2 x the recommended dose) and application of efficient microorganisms (presence and absence), thus totaling 32 pots. At 90 days after transplanting, the following variables were evaluated: stem diameter, plant height, leaf blade length, number of leaves, total foliage dry mass, root dry mass, root volume and shoot/root ratio. Inoculation with efficient microorganisms maximized the development of cashew tree seedlings. Molasses did not influence in the development of cashew tree seedlings.